Missing an osteoporotic vertebral fracture. - Cheong, Ai Theng; Khoo, Ee Ming (Academy of Family Physicians of Malaysia, 2009)
This case illustrates an 80-year-old lady who presented with acute low back pain and finally succumbed from complications of osteoporotic vertebral fracture. Among the contributing factors are delayed diagnosis and a lack of continuity of care. It reminds the practitioners of the importance to look out for red flag symptoms and to have a high index of suspicion for vertebral fracture in high risk patients presenting with low back pain.